Economic Minimising environmental impact in the textile industry - Inche Mitma, Jorge Luis (2000)
This study assesses the economic minimization of environmental impact in the textile industry considering the savings in the consumption of inputs, energy and product sales. inputs reuse, reuse of bath scouring and bleaching, and reuse of washing water 3 minimization options were analyzed. economic analysis shows that the reuse of inputs generates profits for the company. shows that an additional 3% in scouring and bleaching baths investment allows cost savings by 50%